THE ROLE OF ENGLISH COMMUNICATION TRAINING FOR SMES AT DHARMAWANGSA UNIVERSITY - Sarah Nasution; Asrindah Nasution (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2026)
This research aims to describe the forms of support provided by English language communication training to Micro, Small and Medium Enterprises (MSMEs) mentored by Dharmawangsa University. A qualitative approach was used to explore in depth the experiences of MSMEs involved in the university’s mentoring programme. Data were collected through semi-structured interviews with five trainers, three mentors, and ten MSME operators actively participating in business incubation activities. The findings indicate that the support provided encompasses business management training, guidance on digital marketing, as well as administrative and legal support for business operations. The MSME operators acknowledged that the university’s ongoing mentoring has had a positive impact on enhancing their business capacity and ensuring the sustainability of their enterprises. This study concludes that the active role of English language communication training is crucial in building a campus entrepreneurship ecosystem that empowers local SMEs.